The news of the Twelver Salafism (Journal of the College of Basic Education, 2023)
The student of the history of Islamic jurisprudence in general and the jurisprudence of the Twelver Shiites in particular must take a pause for contemplation in front of the news from the Twelver Shiites. Fundamentalists put it to derive the legal ruling such as unanimity, reason and analogy.